Shortening of primary cilia length is associated with urine concentration in the kidneys - Min Jung Kong; Sang Jun Han; Sung Young Seu; Ki-Hwan Han; Joshua H. Lipschutz; Kwon Moo Park (Kidney Research and Clinical Practice, 2023)
Background The primary cilium, a microtubule-based cellular organelle present in certain kidney cells, functions as a mechano-sensor to monitor fluid flow in addition to various other biological functions. In kidneys, the primary cilia protrude into the tubular lumen and are directly exposed to pro-urine flow and components. However, their effects on urine concentration remain to be defined. Here, we investigated the association between primary cilia and urine concentration. Methods Mice either had free access to water (normal water intake, NWI) or were not allowed access to water (water deprivation, WD). Some mice received tubastatin, an inhibitor of histone deacetylase 6 (HDAC6), which regulates the acetylation of α-tubulin, a core protein of microtubules. Results WD decreased urine output and increased urine osmolality, concomitant with apical plasma membrane localization of aquaporin 2 (AQP2) in the kidney. After WD, compared with after NWI, the lengths of primary cilia in renal tubular epithelial cells were shortened and HDAC6 activity increased. WD induced deacetylation of α-tubulin without altering α-tubulin levels in the kidney. Tubastatin prevented the shortening of cilia through increasing HDAC6 activity and consequently increasing acetylated α-tubulin expression. Furthermore, tubastatin prevented the WD-induced reduction of urine output, urine osmolality increase, and apical plasma membrane localization of AQP2. Conclusions WD shortens primary cilia length through HDAC6 activation and α-tubulin deacetylation, while HDAC6 inhibition blocks the WD-induced changes in cilia length and urine output. This suggests that cilia length alterations are involved, at least in part, in the regulation of body water balance and urine concentration.